Transportation Network Vehicle System – Human Resource 1 (New Hire on Board, Social Recognition, Applicant Management, Recruitment): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The HR1 system manages employees as valuable assets to a business. It provides passengers important information such as the fare, the ride's plate number, and the driver's name. The system also offers insights into its functions and services for employees and passengers. Moreover, it keeps records of employee performance to ensure quality service meets passenger expectations. Agile methodology is a collaborative software development technique that involves clients and end-users in the process. This conceptual framework adds pragmatism to the delivery of the final product. Sprints are specific project phases completed within a set amount of time. A new system has been developed in response to challenges faced by scrum teams, which transportation firms like Grab and Uber can use.